The correlation between the severity of cerebral microbleeds and serum HMGB1 levels and cognitive impairment in patients with cerebral small vessel disease - Wang, Minghua; Liu, Junli; Wang, Fan; Li, Qing; Zhang, Jian; Ji, Sibei; Li, Shaomin; Lu, Chengbiao; Zhao, Jianhua (Frontiers in Aging Neuroscience, 2023)
Objective The study investigated the correlation and predictive value between the severity of cerebral microbleeds (CMBs) and the level of serum High Mobility Group Protein B1 (HMGB1) and the occurrence of cognitive impairment in patients with cerebral small vessel disease (CSVD). Methods A total of 139 patients with CSVD admitted to the Department of Neurology of the First Affiliated Hospital of Xinxiang Medical University from December 2020 to December 2022 were selected as study subjects. The Montreal Cognitive Assessment (MoCA) scale was used to assess the cognitive function and was divided into the cognitive impairment group and the cognitive normal group. Magnetic Resonance Imaging (MRI) and Susceptibility Weighted Imaging (SWI) were used to screen and assess the severity of CMBs. Serum HMGB1 levels of CSVD patients were measured by enzyme linked immunosorbent assay (ELISA). Multivariable logistic regression analysis was used to explore risk factors for cognitive impairment and CMBs. Pearson correlation analysis was used to investigate the correlation between HMGB1 and cognitive function. Receiver Operating Characteristics (ROC) curves were used to assess the predictive value of HMGB1 for the occurrence of cognitive impairment in patients with CMBs. Results High Mobility Group Protein B1, uric acid (UA), glycosylated hemoglobin (HbA1c), CMBs, lacunar cerebral infarction (LI), years of education, and history of hypertension were risk factors for cognitive impairment (P < 0.05); HMGB1 was significantly and negatively associated with total MoCA score, visuospatial/executive ability, and delayed recall ability (P < 0.05). HMGB1 was significantly and positively correlated with the number of CMBs (P < 0.05). The area under the ROC curve for HMGB1 predicting cognitive impairment in patients with CMBs was 0.807 (P < 0.001). Conclusion Serum HMGB1 levels are associated with the development of cognitive impairment in CSVD patients, and serum HMGB1 levels have a high predictive value for the development of cognitive impairment in CSVD patients with combined CMBs, which can be used for early clinical identification and intervention of vascular cognitive impairment.